Evaluasi Produksi Pengupasan Overburden di Tambang Batubara Pit KAI 1 PT Kurnia Alam Investama Kecamatan Batin XXIV, Kabupaten Batanghari, Provinsi Jambi - Muhammad Rizky Amendra; Iswandaru; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Karunia Alam Investama is a coal mining company located in Hajran Village, Batin xxiv District, Batanghari Regency, Jambi Province. The applied mining system is an open pit mining system with top loading and its loading pattern. The loading process is carried out using the Hitachi zaxis excavator and the transport people using the Scania P360 Dump Truck. The hauling distance from the mining front to the dumping area is 150 ±. The problem that occurs is that the production target of 88385.9 BCM/month has not been achieved from the actual calculation of overburden production, based on the calculation results it can be seen that the production is 76038.77 BCM/month. The data collected is in the form of conveyor load time, conveyance cycle time, swelling factor, bowl filling factor, roads, work resistance, mechanical device specifications. Efforts were made to achieve the production target, namely by increasing the effective working time from the time constraint so that the work efficiency of the conveyance increased from 60.39% to 64.59% and the addition of 1 unit of Dump Truck Scania P360 conveyance. so that production increased from 76038.77 BCM/month to 92957.24 BCM/month. Abstrak. PT Karunia Alam Investama merupakan sebuah perusahaan pertambangan batubara yang berlokasi Desa Hajran Kecamatan Batin xxiv, Kabupaten Batanghari, Provinsi Jambi. Sistem penambangan yang diterapkan adalah sistem tambang terbuka dengan dan pola pemuatannya yaitu top loading. Proses pemuatan dilakukan dengan menggunakan Excavator hitachi zaxis dan peroses pengangkutan menggunakan Dump Truck Scania P360 . Jarak angkut dari front penambangan menuju dumping area 150 ±. Permasalahan yang terjadi adalah belum tercapainya target produksi sebesar 88385,9 BCM/Bulan dari perhitungan produksi overburden dilakukan secara aktual, berdasarkan hasil perhitungan dapat bahwa produksi sebesar 76038,77 BCM/Bulan. Data yang dikumpulkan berupa waktu edar alat muat, waktu edar alat angkut, faktor pengembangan, faktor pengisian mangkuk, jalan, hambatan kerja, spesifikasi alat mekanis. Upaya yang dilakukan agar target produksi tercapai yaitu dengan meningkatkan waktu kerja efektif dari waktu hambatan sehingga efisiensi kerja alat angkut meningkat dari 60,39% menjadi 64,59% dan penambahan 1 unit alat angkut Dump Truck Scania P360. sehingga produksinya meningkat dari 76038,77 BCM/Bulan menjadi 92957,24 BCM/Bulan.